The GABAA antagonist bicuculline attenuates progesterone-induced memory impairments in middle-aged ovariectomized rats - Braden, B. Blair; Kingston, Melissa L.; Koenig, Elizabeth N.; Lavery, Courtney N.; Tsang, Candy W. S.; Bimonte-Nelson, Heather A. (Frontiers in Aging Neuroscience, 2015)
In women, high levels of natural progesterone have been associated with detrimental cognitive effects via the “maternal amnesia” phenomenon as well as in controlled experiments. In aged ovariectomized (Ovx) rats, progesterone has been shown to impair cognition and impact the GABAergic system in cognitive brain regions. Here, we tested whether the GABAergic system is a mechanism of progesterone’s detrimental cognitive effects in the Ovx rat by attempting to reverse progesterone-induced impairments via concomitant treatment with GABAA antagonist, bicuculline. Thirteen month old rats received Ovx plus daily vehicle, progesterone, bicuculline, or progesterone+bicuculline injections beginning two weeks prior to testing. The water radial-arm maze was used to evaluate spatial working and reference memory. During learning, rats administered progesterone made more working memory errors than those administered vehicle, and this impairment was reversed by the addition of bicuculline. The progesterone impairment was transient and all animals performed similarly by the end of regular testing. On the last day of testing, a six-hour delay was administered to evaluate memory retention. Progesterone-treated rats were the only group to increase working memory errors with the delay; the addition of bicuculline prevented the progesterone-induced impairment. The vehicle, bicuculline, and progesterone+bicuculline groups were not impaired by the delay. The current rodent findings corroborate prior research reporting progesterone-induced detriments on cognition in women and in the aging Ovx rat. Moreover, the data suggest that progesterone-induced cognitive impairment is, in part, related to the GABAergic system. Given that progesterone is included in numerous clinically-prescribed hormone therapies and contraceptives (e.g. micronized), and as synthetic analogs, further research is warranted to better understand the parameters and mechanism(s) of progesterone-induced cognitive impairments.